THE ECONOMIC ESSENCE OF THE STAFF TRAINING SYSTEM IN THE AGRICULTURAL SECTOR - Boltayev, Nurali Shiramatovich (THE INNOVATION ECONOMY, 2026)
In the article, it will be possible to achieve economic growth by training qualified personnel in the agricultural sector and applying scientifically based recommendations in the field, systematizing scientific and practical mechanisms based on knowledge, and creating an interconnected system. Scientific and practical recommendations have been developed on the directions of economic impact of personnel training in the agricultural sector, its significance, results and advantages, the importance of economic mechanisms and the incentive system between the university and the employer in personnel training.